Pulmonary choristoma associated with calf meningocele - Diego Medeiros de Oliveira (Ciência Rural, 2009)
Pulmonary choristoma is a rare malformation reported in different animal species defined as a mass of normal histological pulmonary tissue in an abnormal location. A case of pulmonary choristoma and meningocele is reported in a calf that presented a fluctuating subcutaneous fluid containing mass, measuring 15 x 15 x 20cm in the skull frontal region. The skin covering the sac was surgically removed. Macroscopically, subcutaneous nodules up to 2cm in diameter with irregular whitish areas mixed with red areas were observed. In the histological examination, pulmonary lobules tissue composed by alveoli, bronchi, bronchioles and cartilage were observed. Dilated blood vessels and hemorrhages were present between the lobules. In this case the pulmonary choristoma was associated with meningocele, and probably was the mechanical cause for the failure of the skull closure.